2019
DOI: 10.1177/1098612x19826715
|View full text |Cite
|
Sign up to set email alerts
|

Use of nalbuphine as a substitute for butorphanol in combination with dexmedetomidine and tiletamine/zolazepam: a randomized non-inferiority trial

Abstract: Objectives The goal of this study was to determine whether a drug combination using nalbuphine with dexmedetomidine and tiletamine/zolazepam is non-inferior to one that uses butorphanol. Methods All healthy cats presenting solely for gonadectomy to two trap–neuter–return mobile clinic days were randomly assigned to induction with a combination of tiletamine/zolazepam 3 mg/kg, dexmedetomidine 7.5 µg/kg and either butorphanol or nalbuphine at 0.15 mg/kg. All participants were blinded to the identity of the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The calm recovery without agitation associated with nalbuphine administration could be attributed to the fact that nalbuphine primarily acts on c-fiber nociceptors, not motor or sympathetic receptors [ 25 ]. In cats, nalbuphine-based anesthetic combination has also been shown to provide superior clinician satisfaction during gonadectomy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The calm recovery without agitation associated with nalbuphine administration could be attributed to the fact that nalbuphine primarily acts on c-fiber nociceptors, not motor or sympathetic receptors [ 25 ]. In cats, nalbuphine-based anesthetic combination has also been shown to provide superior clinician satisfaction during gonadectomy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the XK group, the XNK group showed a lower level of cortisol at TInd, TE (0), and ½, 1, 2, 4, 6, 12, and 24 h postoperatively, with a statistically significant decrease detected at ½ and 1 h timepoints. In prior studies, nalbuphine has been reported to enhance postoperative analgesia and decrease surgical stress and pain [ 7 , 31 , 42 ], which could be pivotal for reducing cortisol release. In this current study, the subjective immediate postoperative pain score almost correlated with the dynamic alteration which occurred in the serum cortisol concentration in both inductions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nalbuphine counteracts the respiratory depression of α 2 ‐agonists and provides additional analgesic effect (Schmidt et al 1985, Mills et al 1990, Kamal et al 2019). Although dexmedetomidine and nalbuphine have not been used together on river otters, they have been on dogs, cats, and humans (Nallam et al 2017, Nishimura et al 2018, Kreisler et al 2020) and in combination with other drugs for other otter species (Joseph et al 1987, Fiorello et al 2014). Medetomidine (Domitor® [medetomidine hydrochloride, Pfizer Animal Health, New York, NY, USA) is a drug closely related to dexmedetomidine (Ko et al 2009, Hoy and Keating 2011) and has been used to sedate otters in several studies (Spelman et al 1994, Fernandez‐Moran et al 2001, Soto‐Azat et al 2004, Soto‐Azat et al 2006).…”
mentioning
confidence: 99%